2018
DOI: 10.1164/rccm.201708-1613oc
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Responses to Ozone Exposure. MOSES (The Multicenter Ozone Study in Older Subjects)

Abstract: Exposure to ozone at near ambient levels induced lung function effects, airway injury, and airway inflammation in older healthy adults. Clinical trial registered with www.clinicaltrials.gov (NCT01487005).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Ozone enhanced plasma CC16 levels and sputum neutrophilia in a dose-dependent manner after 4 h and sputum neutrophil counts correlated with airway biopsy counts (56). Sputum neutrophilia returned to normal levels 18 h post-ozone exposure (55, 56). Worryingly, concentrations of ozone close to the National Ambient Air Quality Standard (0.06 ppm) decreased lung function and increased airway inflammation in healthy young adults (57).…”
Section: Epidemiological Impact Of Ozone In Healthy and At Risk Subjectsmentioning
confidence: 93%
See 1 more Smart Citation
“…Ozone enhanced plasma CC16 levels and sputum neutrophilia in a dose-dependent manner after 4 h and sputum neutrophil counts correlated with airway biopsy counts (56). Sputum neutrophilia returned to normal levels 18 h post-ozone exposure (55, 56). Worryingly, concentrations of ozone close to the National Ambient Air Quality Standard (0.06 ppm) decreased lung function and increased airway inflammation in healthy young adults (57).…”
Section: Epidemiological Impact Of Ozone In Healthy and At Risk Subjectsmentioning
confidence: 93%
“…Controlled exposure studies support these epidemiological reports. The recent Multicenter Ozone Study in Older Subjects (MOSES) examined the respiratory responses to low concentrations of ozone in 87 healthy adults aged 60 years (55). Exposure to filtered air rapidly increased mean FEV 1 and FVC values but ozone attenuated these increases in a dose-dependent manner.…”
Section: Epidemiological Impact Of Ozone In Healthy and At Risk Subjectsmentioning
confidence: 99%
“…Secondary outcomes included markers of oxidative stress and endothelial function. Ozone effects on pulmonary and cardiovascular function in this study are reported elsewhere [34–36].…”
Section: Introductionmentioning
confidence: 90%
“…Many previous studies also claimed that air pollutants like carbon monoxide, NO 2 , particulate matter (PM) in dissimilar fractions such as PM 0.1 μm, PM 2.5 μm and PM 10 μm, polycyclic aromatic hydrocarbons, volatile organic compounds, and O 3 pollution, etc. Adversely affect the immune and cardio-respiratory systems of the host by altering their resistance to various bacterial and viral infections ( Arjomandi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%